2019
DOI: 10.3390/membranes9090114
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study on Enzymatic-Based Cleaning of Cation-Exchange Membranes Used in Electrodialysis System in Red Wine Production

Abstract: The use of enzymatic agents as biological solutions for cleaning ion-exchange membranes fouled by organic compounds during electrodialysis (ED) treatments in the food industry could be an interesting alternative to chemical cleanings implemented at an industrial scale. This paper is focused on testing the cleaning efficiency of three enzyme classes (β-glucanase, protease, and polyphenol oxidase) chosen for their specific actions on polysaccharides, proteins, and phenolic compounds, respectively, fouled on a ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…They performed well in the case of cleaning of ultrafiltration membranes fouled by proteins [196] or in the case of reducing membrane fouling in bioreactors [197]. Bdiri et al [198] first tested protease and β-glucanase, as well as polyphenol oxidase, which enter the specific interactions with proteins, polysaccharides, and phenolic compounds, respectively, as well as mixtures of these enzymes. They showed that the use of these cleaning agents can increase the conductivity and exchange capacity of the wine-fouled CMX-Sb cation-exchange membrane by at least 25% and 12%, respectively.…”
Section: Non-destructive Methods Of Membrane Fouling Controlmentioning
confidence: 99%
“…They performed well in the case of cleaning of ultrafiltration membranes fouled by proteins [196] or in the case of reducing membrane fouling in bioreactors [197]. Bdiri et al [198] first tested protease and β-glucanase, as well as polyphenol oxidase, which enter the specific interactions with proteins, polysaccharides, and phenolic compounds, respectively, as well as mixtures of these enzymes. They showed that the use of these cleaning agents can increase the conductivity and exchange capacity of the wine-fouled CMX-Sb cation-exchange membrane by at least 25% and 12%, respectively.…”
Section: Non-destructive Methods Of Membrane Fouling Controlmentioning
confidence: 99%
“…With respect to total tannins, the treatment that most negatively affected its concentration was ED followed by IER and CS. Lasanta et al [15] also reported a slight decrease in the total tannin content of wines stabilized by cation exchange resin and Bdiri et al [43] an adsorption of high molecular weight compounds in the ED membranes.…”
Section: Chromatic and Phenolic Parametersmentioning
confidence: 96%
“…Gómez-Benítez et al [40] also reported a decrease in color intensity in cold-stabilized wines. The decrease in chromatic parameters in the wine treated by electrodialysis could be due to the adsorption of high molecular weight compounds in the membranes, as described by Bdiri et al [43]. Some of these compounds, such as polysaccharide polymers, prevent tannin aggregation and precipitation and their elimination could facilitate a decrease in color intensity [44,45].…”
Section: Chromatic and Phenolic Parametersmentioning
confidence: 99%
“…Enzymes have a three-dimensional protein structure that react very specifically on its substrate with catalytic properties [47] which makes their action specific to the nature of each foulant. To date, enzymes are not communally used for the cleaning of IEMs and, to our knowledge, a single scientific research on the enzymatic cleaning of IEMs were reported by Bdiri et al [48]. CMX-Sb (Neosepta, Japan) at advanced stage of fouling by red wine during ED treatments were cleaned by three different kinds of enzymes; a β-glucanase for the hydrolysis of osidic bonds in polysaccharide (Rohalase® BX-BXL), a neutral protease for the hydrolyses of high molecular protein into low molecular peptides (Corolase® 7089) and a Tyrosinase that principally catalyze the oxidation of mono-and di-phenolic compounds oxidation, phenolic acids and polyphenolic substrates.…”
Section: Enzymatic Cleaningsmentioning
confidence: 99%
“…Evolution of the electrical conductivity κ m (t) for the treated CMX-Sb vs. incubation temperature and concentration of the three enzymatic solutions (from[48])…”
mentioning
confidence: 99%